Chinese bayberry (Myrica rubra) phenolics mitigated protein glycoxidation and formation of advanced glycation end-products: A mechanistic investigation. (1st November 2021) - Zhang, Qiaozhi; Huang, Zhijie; Wang, Yong; Wang, Yanbo; Fu, Linglin; Su, Laijin
Graphical abstract: Highlights: Phenolic composition in four common Chinese bayberry cultivars was characterized. Anti-glycation property of CBEs was explored in multiple in vitro model systems. Antioxidant ability of CBEs strongly contributed to their anti-glycative effects. Binding forces between CBEs and BSA correlated with their anti-AGE properties. Constitutive phenolics in CBEs trapped α-dicarbonyl compounds to form adducts. Abstract: Protein glycation and formation of advanced glycation end-products (AGEs) impose threats to the human health. This study firstly investigated the inhibition of Chinese bayberry ( Myrica rubra ) phenolics on AGEs formation through mechanistic analysis. Four common Chinese bayberry cultivars were selected to prepare phenolic-rich extracts (CBEs) and characterized for phenolic composition, and their anti-AGE properties were evaluated in multiple in vitro systems. Total sixteen phenolics were quantified in CBEs by UPLC-ESI-MS/MS. CBEs reduced total and specific fluorescent AGEs formation in various simulating models, and protected the protein from structural modification, oxidation, and cross-linking. Mechanistic analysis unveiled that scavenging of free radicals, inactivation of transition metals, interaction with protein to form complexes, and trapping of reactive α-dicarbonyls to form adducts underlain the mechanisms of the anti-glycative actions of CBEs. Chinese bayberry fruits, especially the cultivars Biqi and Wuzi, may be a promising dietary strategy to mitigate AGEs load in the human body.